QuitNic: A Pilot Randomized Controlled Trial Comparing Nicotine Vaping Products With Nicotine Replacement Therapy for Smoking Cessation Following Residential Detoxification. Issue 3 (8th August 2020) - Bonevski, Billie; Manning, Victoria; Wynne, Olivia; Gartner, Coral; Borland, Ron; Baker, Amanda L; Segan, Catherine J; Skelton, Eliza; Moore, Lyndell; Bathish, Ramez; Chiu, Simon; Guillaumier, Ashleigh; et al.
Abstract: Introduction: The QuitNic pilot trial aimed to test the feasibility of providing a nicotine vaping product (NVP) compared with combination nicotine replacement therapy (NRT) to smokers upon discharge from a smoke-free residential substance use disorder (SUD) treatment service. Methods: QuitNic was a pragmatic two-arm randomized controlled trial. At discharge from residential withdrawal, 100 clients received telephone Quitline behavioral support and either 12-week supply of NRT or an NVP. Treatment adherence and acceptability, self-reported abstinence, cigarettes smoked per day (CPD), frequency of cravings, and severity of withdrawal symptoms were assessed at 6 and 12 weeks. Results are reported for complete cases and for abstinence outcomes, penalized imputation results are reported where missing is assumed smoking. Results: Retention on was 63% at 6 weeks and 50% at 12 weeks. At 12 weeks, 68% of the NRT group reported using combination NRT while 96% of the NVP group used the device. Acceptability ratings for the products were high in both groups. At 12 weeks, 14% of the NVP group and 18% of the NRT group reported not smoking at all in the last 7 days. Mean CPD among continued smokers decreased significantly between baseline to 12 weeks in both groups; from 19.91 to 4.72 for the NVP group ( p < .001) and from 20.88 to 5.52 in the NRT group ( p < .001). Cravings and withdrawal symptoms significantly decreased for both groups. Conclusions: Clients completing residential withdrawal readily engaged with smoking cessation post-treatment when given the opportunity. Further research is required to identify the most effective treatments postwithdrawal for this population at elevated risk of tobacco-related harm. Trial registration number: ACTRN12617000849392 Implications: This pilot study showed that smoking cessation support involving options for nicotine replacement and Quitline-delivered cognitive behavioral counseling is attractive to people after they have been discharged from SUD treatment. Both nicotine vaping products and nicotine replacement therapies were highly acceptable and used by participants who reported reductions in cravings for cigarettes and perceptions of withdrawal symptoms and reductions in number of cigarettes smoked. Some participants self-reported abstinence from cigarettes—around one in five reported having quit smoking cigarettes at 12 weeks postdischarge. The results have significant public health implications for providing quit support following discharge from SUD treatment.